Penerapan Sustainable Event Management Pada Kegiatan Special Event Ephics 3.0 di Politeknik Pariwisata Prima Internasional - Widia Ningsi; Toni Ari Wibowo (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
The EPHICS 3.0 Special Event is an event held periodically, namely once a year from 2024 at the Prima International Tourism Polytechnic, Cirebon, West Java. When this Special Event activity is carried out in a way that is in accordance with government directions, namely in line with the concept of sustainability, it will be able to give a positive impression for partners to get involved. By implementing the sustainable concept, this is also an effective way and will help to introduce that event. what we hold is different from other events, so that the image of the event itself is positive. In implementing sustainable concepts such as responsible, greening, environmentally friendly, corporate social responsibility, social & culture and economic, organizers do not only focus on personal interests but pay attention to several things that need to be considered so that they benefit both parties. The method used in this research is a qualitative approach with descriptive methods. There were informants including the Chief Executive of EPHICS 3.0, the Event Organizing Committee, the Organizing Committee, University Management, organizers and Tenants. The results obtained in this research are that Event EPHICS 3.0 has implemented the concept of Sustainable Event Management, but there are still several concepts that must be fulfilled so that its implementation can be implemented as optimally as possible.